Fabrication of a metal-organic framework composite for removal of Aflatoxin B1 from water. Issue 1 (February 2021) - Samuel, Melvin S.; Kirankumar, V.S.; Selvarajan, E.
Abstract: The Aflatoxins are considered to be poisonous carcinogens as well as mutagens that are regularly found as a contaminant in the improperly stored commodities like the cottonseed, sesame seeds, cassava, chili peppers, sorghum, millet, peanuts, rice, sunflower seeds, sweetcorn, tree nuts, wheat, etc. The Aflatoxins are toxic metabolites that are capable of causing damages to the human as well as animal health by targeting the vital organs. Hence there is dire need to develop novel strategies for the development of the techniques for detoxification to produce contaminant free commodities. The Zinc terephthalate metal-organic framework [Zn(BDC)(DMF)]MOF catalyst prepared using the solvothermal method. In this study, Zn based MOF crystals funtionalized with amines were synthesized for the effective adsorption of the AFB1 and were characterized by the employment of SEM, FTIR, PXRD, BET and UV-DRS. In this study, the Zn(BDC)(DMF)MOF was employed as an adsorbent for the elimination of the Aflatoxin B1 (AFB1) from water. The maximum adsorption capacity of NH2 -Zn(BDC)(DMF)MOF composite for AFB1 was found to be 73.4 mg/g at 303 K and 6.0 pH conditions. The Langmuir and Freundlich isotherms were found to fit well in defining the adsorption performance as well as the kinetic data by the application of a pseudo-second-order model. The results reported that NH2 -Zn(BDC)(DMF)MOF can be employed as a suitable candidate capable of acting as an adsorbent for the removal AFB1. Graphical Abstract: ga1 Highlights: Zn based MOF crystals functionalized with amines were synthesized. NH2 -Zn(BDC)(DMF)MOF were characterized by the employment of SEM, FTIR, PXRD, BET and UV-DRS. NH2 -Zn(BDC)(DMF)MOF can be restored and recycled. NH2 -Zn(BDC)(DMF)MOF can be employed as a suitable candidate capable of acting as an adsorbent for the removal AFB1.